Female sexism and religion linking to value and cultural norms - Yumas, Gabriella Mutiara (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
Instances of sexism, a widespread manifestation of gender bias, frequently lead to the belief that one gender is superior or inferior. This is evident through attitudes, behaviors, and institutional procedures that support gender hierarchies and sustain unequal treatment. The entertainment sector, by virtue of its extensive impact, intensifies these biases by molding public attitudes towards women. Through the lens of Glick and Fiske's ambivalent sexism theory, this study investigates the sexism Kim Kardashian encounters on social media sites, namely Instagram, by analyzing both hostile and benevolent sexism. Therefore, the aim of this study is to investigate the recurring victimization of the Kardashian family based on sexist ideologies. This study uses a qualitative research approach, specifically case study approaches, to investigate the phenomenon of sexism encountered by Kim Kardashian. Investigators will collect data using interviews, questionnaires, live observations, and a comprehensive review of relevant papers, journals, and prior studies. The main objective of this study is to gather data from social media platforms, focusing specifically on evaluating commentary that exhibits sexism, hate speech, patriarchy, misogyny, discrimination, and related subjects on Kim Kardashian's Instagram account. Through the lens of The Ambivalent Sexism Theory, this study reveals that Kim Kardashian evokes both angry and pleasant sexist behavior in Instagram comments.